UPAYA WORLD WIDE FUND FOR NATURE WWF DALAM MENGKAMPANYEKAN SAVE OUR SHARK (SOS) DI INDONESIA TAHUN 2013-2015 - Tria Sani Saputri; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Sharks are apex predators (top predators) that are very influential as holders of food chain control in marine ecosystems. But now the shark population has begun to be threatened, the reason is that Overfishing is done. Because the demand for fin has a high price. In this paper theoretically arranged through a green thought perspective, the level of behavior-group analysis and international organization theory and guided by qualitative research methods. The scope of this research is how the efforts made by WWF in the soshark campaign in Indonesia. WWF (World Wildlife Fund For Nature) made various efforts to overcome the extinction of sharks from the threat of shark finning practices. Starting from a campaign called SOSHARKS (Save Our Sharks) in 2013-2015, collecting petitions, checking menus at hotels and restaurants in Indonesia and organizing sharks and rays symposiums with the Indonesian Ministry of Maritime Affairs and Fisheries.Keywords: sharks, SOShark campaign, WWF efforts